2001
DOI: 10.1023/a:1017580329538
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Homeless individuals have a very high risk of TB infection and disease and contact investigation requires specific methods for them. Programmes of screening and supervised treatment should be ensured in this group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…There was only one case-control study; for the five cross-sectional studies that were included, we found minimal heterogeneity ( I 2 = 0%). We also stratified studies that used different cutoffs for the TST; among those analyses that used induration size of 5 mm as the cutoff for a positive test [32,33], the pooled OR for latent TB was 2.08 (95% CI, 1.53–2.83), while among those that used a 10 mm cutoff [30,31,34,35], the pooled OR was 1.83 (95% CI, 1.49–2.23). When we stratified on other quality-associated study characteristics, we found that ORs for TB infection were lower among studies that adjusted for alcohol (Table 2), but that a positive effect of smoking on latent TB remained.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There was only one case-control study; for the five cross-sectional studies that were included, we found minimal heterogeneity ( I 2 = 0%). We also stratified studies that used different cutoffs for the TST; among those analyses that used induration size of 5 mm as the cutoff for a positive test [32,33], the pooled OR for latent TB was 2.08 (95% CI, 1.53–2.83), while among those that used a 10 mm cutoff [30,31,34,35], the pooled OR was 1.83 (95% CI, 1.49–2.23). When we stratified on other quality-associated study characteristics, we found that ORs for TB infection were lower among studies that adjusted for alcohol (Table 2), but that a positive effect of smoking on latent TB remained.…”
Section: Resultsmentioning
confidence: 99%
“…Another possible source of outcome misclassification was suggested by Plant and colleagues [32], who noted that the frequency of small induration sizes among TSTs was higher among smokers than nonsmokers, suggesting that smokers may be less capable than nonsmokers of eliciting a vigorous skin test reaction and that latent TB infection in smokers may thus be underdetected when the 10 mm cutoff is used. Despite this possible limitation, we found that the two studies of latent infection that used 5 mm cutoffs for the TST [32,33] reported effects that were not statistically different from those that used 10 mm [30,31,34,35]. Finally, the diagnosis of TB in children is notoriously difficult; if children exposed to passive smoke were more likely to be successfully diagnosed with disease than those who were not, this might have introduced a bias that would explain the strong positive association between passive smoking and TB.…”
Section: Discussionmentioning
confidence: 99%
“…In Frankfurt, implementing a voluntary X-ray screening program with the help of local social services had a positive impact on participation and coverage [5]. Other studies showed how cooperation between health and social sectors helps to promote health opportunities for underserved groups of population [8, 25]. As opposed to other infectious diseases, involving peer educators does not seem effective in increasing homeless persons participation screening campaigns for active TB.…”
Section: Discussionmentioning
confidence: 99%
“…In spite of the accumulated evidence demonstrating a causal relationship between smoking and TB infection, whether smoking cessation in a community level could contribute to TB controlling is still being debated. Because most of the published studies were limited to special populations at high risk of TB infection, including prisoners [89], migrant workers [1011], immigrants [1213], and the homeless [14]. Furthermore, several studies even reported a negative association between cigarette smoking and TB infection [1517].…”
Section: Introductionmentioning
confidence: 99%